2016
DOI: 10.1007/s11664-016-4463-z
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Si Bulk Crystals with Large Diameter Ratio Using Small Crucibles by Creating a Large Low-Temperature Region Inside a Si Melt Contained in an NOC Furnace Developed Using Two Zone Heaters

Abstract: Three zone heaters were generally used for a noncontact crucible (NOC) furnace. For practical reasons a simpler NOC furnace was developed with two zone heaters, which had a carbon heat holder to cover the three roles of each heater. Large low-temperature regions were obtained, and silicon ingots were grown in small crucibles with a large diameter and diameter ratio. Here, the diameter ratio is the ratio of the ingot diameter to the crucible diameter and can be as large as 0.90. The diameter ratio was controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The publication reported that the diameter ratio crystal/crucible was not much affected by the size of the crucible but mainly by the temperature decrease which shows great perspectives for the growth of larger diameter ingots. The reported oxygen contamination was quite low 1 × 10 18 cm −3 . A published work by Youssef et al showed that swirl defect rings in silicon can be formed in both CZ and Non‐contact method processes.…”
Section: Introductionmentioning
confidence: 94%
“…The publication reported that the diameter ratio crystal/crucible was not much affected by the size of the crucible but mainly by the temperature decrease which shows great perspectives for the growth of larger diameter ingots. The reported oxygen contamination was quite low 1 × 10 18 cm −3 . A published work by Youssef et al showed that swirl defect rings in silicon can be formed in both CZ and Non‐contact method processes.…”
Section: Introductionmentioning
confidence: 94%